Islamic Philanthropy and Humanitarianism: Hybridity and Institutional Dynamics of PKPU in the Landscape of Islamic Humanitarianism - Hidayat, Romdlon; Fauzia, Amelia; Kailani, Najib (AL-TAHRIR, 2024)
This research aims to examine the phenomenon of transformation and hybridity practices in Islamic philanthropic institutions in Indonesia by carrying out research at the Pos Keadilan Peduli Umat (PKPU) from 2001 to 2023. This research employs a qualitative method, utilizing in-depth interview methods, observation, and institutional document analysis. The theoretical approach employed is the hybridity of Homi K. Bhabha, which is moderately helpful in explaining how Islamic philanthropic institutions have a role between two poles of values, namely normative Islamic values and global humanitarian values. This theoretical research also uses Marie Juul Petersen's institutional criticism model  to comprehend institutional integration, differentiation, and dynamics. The results of this research indicate that PKPU fundamentally changed its institution into the Human Initiative (HI) to take advantage of the global humanitarian market, expand humanitarian work, and manage institutions in the style of Western management by renegotiating its institutional identity while remaining spiritual but professional, Islamic but universal and able to connect to the global community. The PKPU also established two institutions, the Indonesian Zakat Initiative (IZI) and the Waqf Initiative (IWakaf), to focus on developing the potential of zakat and waqf for Muslims in Indonesia. The changes in PKPU show a dynamic, synergistic, and adaptive institutional development model to extend the market and innovation that continues to grow in humanitarian and development contributions.